2010
DOI: 10.2989/17280583.2010.493654
|View full text |Cite
|
Sign up to set email alerts
|

Contested multiple voices of young masculinities amongst adolescent boys in Alexandra Township, South Africa

Abstract: This study reveals that being a boy is not a homogeneous phenomenon. All the participants agreed that there are different ways of being a boy and that some boys are more popular than others, which often depends on the context in which the boys find themselves. The interviews revealed recurring allusions to different 'types' of boys at schools in Alexandra Township-namely, tsotsi boys and academic boys. However, it is important to note that boys do not fit neatly into each of these categories. The findings of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…Some of these learners then start secondary education already older than 14 years, which is the entry age requirement. [15] The resultant wide age range was evident in this study and is a major and ongoing problem.…”
Section: Researchmentioning
confidence: 66%
See 1 more Smart Citation
“…Some of these learners then start secondary education already older than 14 years, which is the entry age requirement. [15] The resultant wide age range was evident in this study and is a major and ongoing problem.…”
Section: Researchmentioning
confidence: 66%
“…[15] Some of the reasons for reluctance to report included fear of being laughed at, being called 'mama's boy' [15] and that reporting such bullying will be followed by intensified actions of bullying. [5] In this study, learners living in informal settlements and RDP houses were more likely to have carried weapons in the past 30 days.…”
Section: Researchmentioning
confidence: 99%
“…This site was chosen for sampling as it is located within Gauteng, which has a HIV prevalence of 11% and also represents the national prevalence of HIV (UNAIDS/WHO, 2013). Furthermore, research has shown that adult men from this population embody varied urban masculinities that occupy spaces of plurality whereby masculine identities simultaneously eliminate and allow traditional hegemonic ideals of patriarchy (Langa, 2010). This space was of particular interest to the researchers as it represented the tension between tradition and medicine as it relates to the meanings of HIV prophylactic VMAMC and TMC.…”
Section: Participantsmentioning
confidence: 99%
“…Thus the hegemonic conception of men's gender identity and in turn masculinity is one in which men are seen as dominant within a patriarchal society, and the suppression of women's agency and power as well as alternative and subordinated expressions of masculinity. Connell's conceptions of sexuality have since been criticised, with many, including Connell herself (Connell and Messerschmidt 2005) noting that hegemonic masculinity changes over time and across cultures, that alternative masculinities have been overlooked, and that masculinity is a fluid concept that shifts in relation to culture, age, race, class and power (Langa 2010;Bhana and Nkani 2014). They nevertheless also argue that within cultures and communities there are dominant markers of what it means to be a man -expectations about behaviour that confirm more or less desirable features of masculinity.…”
Section: Conceptualising Youth and Youth Sexualitymentioning
confidence: 99%